A music sharing platform using an embedded system - Baras Nikolaos; Sideris Dimitrios; Dasygenis Minas (SHS Web of Conferences, 2022)
Due to the rapid growth of technology over the last few decades, the urban e-waste generation rate has constantly been increasing. Discarded electronic appliances such as mobile phones, computers and televisions have caused increasing environmental concerns. Recycling and reusing these products is the only way to make a sustainable environment. In this paper, we propose a low cost system based on the Arduino Nano microcontroller that uses obsolete hardware that would otherwise be considered garbage, such as floppy and disk drives to play music using MIDI files. The system can be used as an instrument in schools to teach students about music, about how sound is produced and also compose music. The cost of the proposed system is lower compared to other implementations found in literature. Finally, we evaluated the performance of the proposed prototype by using a wide range of audio files in different scenarios.